Public in-kind relief and private self-insurance - Timo Goeschl; Shunsuke Managi (University of Heidelberg, Department of Economics, 2017)
In the wake of several high-profile natural disasters, crowding effects between public relief and private investments in disaster preparedness have recently attracted renewed attention. We examine how non-hypothetical self-insurance behavior by households responds to variations in public investments in relief capabilities based on a large disaster preparedness survey (n = 19,071) conducted in Japan in 2012. The preparedness measure used is emergency drinking water storage, defining a setting in which (i) government provides in-kind, rather than cash, relief and (ii) the crowding effect observed is more apt to be total, rather than partial. In contrast to much of the literature studying crowding effects of cash relief, there is little evidence for crowding out in emergency drinking water, with an upper bound of 2 percent at the intensive margin.
urn:nbn:de:bsz:16-heidok-230297
Keywords: D78; D81; G22; Q54; 330; Crowding-out; disaster preparedness; government relief; natural hazards; in-kind relief